2020
DOI: 10.1111/all.14535
|View full text |Cite
|
Sign up to set email alerts
|

Sputum macrophage diversity and activation in asthma: Role of severity and inflammatory phenotype

Abstract: Background Macrophages control innate and acquired immunity, but their role in severe asthma remains ill‐defined. We investigated gene signatures of macrophage subtypes in the sputum of 104 asthmatics and 16 healthy volunteers from the U‐BIOPRED cohort. Methods Forty‐nine gene signatures (modules) for differentially stimulated macrophages, one to assess lung tissue‐resident cells (TR‐Mφ) and two for their polarization (classically and alternatively activated macrophages: M1 and M2, respectively) were studied u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 42 publications
2
26
1
Order By: Relevance
“…This study demonstrated that macrophages provide a critical danger signal in response to allergen exposure, namely APOE, and through this mechanism enhance the adaptive inflammatory response to aeroallergens (165). Similar findings were also reported by Tiotiu et al, based on an analysis of sputum macrophages obtained from 104 asthmatics and 16 healthy volunteers in the U-BIOPRED (Unbiased BIOmarkers in PREDiction of respiratory disease outcomes) asthma cohort (166). In this study, the gene signatures for differentially stimulated macrophages, i.e.…”
Section: Lung Macrophage Diversity and Immune Regulation In Allergic Asthmasupporting
confidence: 89%
See 3 more Smart Citations
“…This study demonstrated that macrophages provide a critical danger signal in response to allergen exposure, namely APOE, and through this mechanism enhance the adaptive inflammatory response to aeroallergens (165). Similar findings were also reported by Tiotiu et al, based on an analysis of sputum macrophages obtained from 104 asthmatics and 16 healthy volunteers in the U-BIOPRED (Unbiased BIOmarkers in PREDiction of respiratory disease outcomes) asthma cohort (166). In this study, the gene signatures for differentially stimulated macrophages, i.e.…”
Section: Lung Macrophage Diversity and Immune Regulation In Allergic Asthmasupporting
confidence: 89%
“…It was found that, although macrophage numbers were significantly lower in severe asthmatics compared to mild/moderate asthmatics and healthy controls, the M2 signature was much higher in severely ill patients. Interestingly, macrophages from severe asthmatics were also enriched for eicosanoid biosynthesis and showed evidence of increased mitochondrial ROS production, implicating macrophages in the maintenance of inflammation and the induction of oxidative stress in cases of severe disease (166). Intriguingly, this study found significant changes in tissueresident macrophage signature enrichment according to asthma severity.…”
Section: Lung Macrophage Diversity and Immune Regulation In Allergic Asthmamentioning
confidence: 51%
See 2 more Smart Citations
“…Macrophages. Lung macrophages play a pivotal role in asthma and COPD [ 111 , 112 ]. Macrophages are abundant in the lung and generate RONS to kill invading pathogens [ 113 , 114 , 115 ].…”
Section: Factors Contributing To Oxidative Stressmentioning
confidence: 99%